1999
DOI: 10.1021/ma9904316
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Micro- and Macrophase Separation of Amphiphilic Block-Copolymers in Aqueous Solution

Abstract: The dynamics of purified poly(ethylene oxide)-block-poly(propylene oxide)-block-poly(ethylene oxide) (PEO−PPO−PEO) block-copolymer micellization and phase separation in aqueous solutions were studied using the iodine laser temperature-jump and stopped flow techniques. The changes in the micellar solutions were followed by either light scattering or fluorescence of 1,6-diphenyl-1,3,5-hexatriene (DPH), which is a probe located in the micelle interior. Three different relaxation processes were observed for the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
191
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(200 citation statements)
references
References 62 publications
8
191
1
Order By: Relevance
“…At the end of simulation, the small micelles and huge micellar clusters coexist. The micellar clusters are also found for other systems in the experiment [64,65] and simulation [66].…”
Section: Resultssupporting
confidence: 58%
“…At the end of simulation, the small micelles and huge micellar clusters coexist. The micellar clusters are also found for other systems in the experiment [64,65] and simulation [66].…”
Section: Resultssupporting
confidence: 58%
“…The self-assembly of such symmetrical amphiphilic triblock copolymers depends sensitively on the sequence of the blocks. [30][31][32] With A representing the hydrophilic block and B the hydrophobic block, ABA block copolymers tend to form core-shell micelles in aqueous solution, [33] while copolymers with a BAB architecture tend to give more complex structures, such as flower-like or interconnected micelles and networks, [34][35][36] which have also been discussed from a theoretical point of view. [37][38][39] Network formation is an important feature which distinguishes BAB block copolymers from self-associated AB diblock chains.…”
Section: Introductionmentioning
confidence: 99%
“…For the samples aged at 55, 60, and 65°C for 30 min, the peak appearing at lower relaxation time is possibly that of unimers/unimer clusters and that appearing above *100 l S is possibly attributed to micelles and micellar clusters/aggregates. The latter could also have been affected by the exchange of unimers with micelles [44]. Further, increasing the ageing temperature above 50°C gave rise to a slight shift of the position of this peak in the relaxation graph to longer periods, suggesting increased aggregation/clustering (Fig.…”
Section: Dls Study Of Hc-ti 4? -Solsmentioning
confidence: 95%
“…The changes in the micellar sizes with temperature show that the micelles are dynamic aggregates in which the individual polymer chains constantly move from one micelle to another. It has already been shown that below *15°C water is a good solvent for PPO, whereas PPO aggregates at high temperatures [44]. On the other hand PEO is dominantly hydrophilic within the temperature range 0 to 100°C.…”
Section: Dls Study Of Hc-ti 4? -Solsmentioning
confidence: 99%